The impact of large classes on the English language learning of economics students at the University of El Salvador, semester II - 2013 - Cardoza Ayala, Alma Patricia
In order to have access to better jobs and to lead successful professional lives in the globalized society we now live, higher education institutions in the country have begun to require their future college graduates to show command of an advanced level of the English language. As a result of these worldwide pressures, more English classes are offered to college students. At the University of El Salvador, the only public college of the country, several English classes are offered. However, these classes are overpopulated, particularly at the School of Economics. Students in large classes do not perform as well as students in small classes (Borden and Burton) The following are some of the most common factors that also have negative impact on the learners: poor classroom management, noise, teaching methodology, didactic material, lack of technological access among others. Teachers of English at the School of Economics have to take into consideration the elements that are related to large classes. In order to reach the outlined objectives during the semester and to improve the quality of student`s learning at the School of Economics as well as to enhance of just taking the subject without any benefit to them. This research contains its corresponding objectives, one general and three specific ones, the definition of the most important terms that will be handled during the project, the method that was used to carry out the research, instrument and techniques that were necessary to collect the data. Also, it is explained how the data collection was codified, the sample and anterior researchers similar to this project that had been carry out in the past years. Recommendations v for the authorities and the teachers have been included in order to improve the teaching- learning process in the School of Economics.